Perceptions of Collaborative Practice and Work Tenure in Relation to Healthcare Workers’ Satisfaction at Amalia Medika Hospital - Nurul Gina Fadlillah; Purwadhi Purwadhi; Mira Veranita (Journal of Economics and Social Sciences (JESS), 2026)
Interprofessional collaboration is an essential component of healthcare delivery and is closely associated with healthcare workers’ satisfaction. This study explores the relationship between healthcare workers’ perceptions of collaborative practice, measured using the Collaborative Practice Assessment Tool (CPAT), work tenure, and job satisfaction at Amalia Medika Hospital. A quantitative correlational design was employed, involving all 123 healthcare workers through a total sampling technique. Data were collected using the CPAT questionnaire and a standardized job satisfaction scale. Multiple linear regression analysis was conducted after meeting classical assumption tests, including normality, multicollinearity, and heteroscedasticity. The results demonstrate that perceptions of collaborative practice are positively and significantly related to job satisfaction (p < 0.05), indicating that stronger perceptions of teamwork are associated with higher satisfaction in daily work activities. In contrast, work tenure shows no significant relationship with job satisfaction (p > 0.05), suggesting that satisfaction is more strongly influenced by factors such as opportunities for self-development, organizational support, and recognition at work. Simultaneously, perceptions of collaborative practice and work tenure are jointly related to job satisfaction, with a coefficient of determination (R²) of 26.9%. Among the two variables, perceptions of collaborative practice exhibit a more dominant association with job satisfaction. These findings underscore the importance of fostering effective interprofessional collaboration as a key strategy for enhancing healthcare workers’ job satisfaction at Amalia Medika Hospital.